Clinical Impact of the Couch Top and Rails on IMRT and Arc Therapy - Pulliam, Kiley B (Phys Med Biol, 2011)
The clinical impact of the Varian Exact Couch on dose, volume coverage to targets and critical structures, and tumor control probability (TCP) has not been described. Thus, we examined their effects on IMRT and arc therapy. Five clinical prostate patients were planned with both, 6-MV 8-field IMRT and 6-MV 2-arc RapidArc using the Eclipse treatment planning system (TPS). These plans neglected treatment couch attenuation, as is a common clinical practice. Dose distributions were then recalculated in Eclipse with the inclusion of the Varian Exact Couch (imaging couch top) and the rails in varying configurations. The changes in dose and coverage were evaluated using the DVHs from each plan iteration. We used a tumor control probability (TCP) model to calculate losses in tumor control resulting from not accounting for the couch top and rails. We also verified dose measurements in a phantom. Failure to account for the treatment couch and rails resulted in clinically unacceptable dose and volume coverage losses to the target for both IMRT and RapidArc. The couch caused average dose losses (relative to plans that ignored the couch) to the prostate of 4.2% and 2.0% for IMRT with the rails out and in, respectively, and 3.2% and 2.9% for RapidArc with the rails out and in, respectively. On average, the percentage of the target covered by the prescribed dose dropped to 35% and 84% for IMRT (rails out and in, respectively) and to 18% and 17% for RapidArc (rails out and in, respectively). The TCP was also reduced by as much as 10.5% (6.3% on average). Dose and volume coverage losses for IMRT plans were primarily due to the rails, while the imaging couch top contributed most to losses for RapidArc. Both the couch top and rails contribute to dose and coverage losses that can render plans clinically unacceptable. A follow-up study we performed found that the less attenuating unipanel mesh couch top available with the Varian Exact couch does not cause a clinically impactful loss of dose or coverage for IMRT but still causes an unacceptable loss for RapidArc. Therefore, both the imaging or mesh couch top and the rails should be accounted for in arc therapy. The imaging couch top should be accounted for in IMRT treatment planning or the mesh top can be used, which would not need to accounted for, and the rails should be moved to avoid the beams during treatment.